Coordinated gripping of substrate by subunits of a AAA+ proteolytic machine - Iosefson, Ohad (Nat Chem Biol, 2015)
Hexameric AAA+ unfoldases of ATP-dependent proteases and protein-remodeling machines use conserved loops that line the axial pore to apply force to substrates during the mechanical processes of protein unfolding and translocation. Whether loops from multiple subunits act independently or coordinately in these processes is a critical aspect of mechanism but is currently unknown for any AAA+ machine. By studying covalently linked hexamers of the E. coli ClpX unfoldase bearing different numbers and configurations of wild-type and mutant pore loops, we show that loops function synergistically, with the number of wild-type loops required for efficient degradation depending upon the stability of the protein substrate. Our results support a mechanism in which a power stroke initiated in one subunit of the ClpX hexamer results in the concurrent movement of all six pore loops, which coordinately grip and apply force to the substrate.